SPIRITUALITAS MODERAT SANTRI PONDOK PESANTREN AMANATUL UMMAH KEMBANGBELOR PACET MOJOKERTO - rozi indrafudddin (Institut Agama Islam Negeri Ponorogo, 2021)
AbstractGeared under qualitative approach, this research aimed at obtaining information about the forms and reasons for moderate spirituality of the students of the Amanatul Ummah Islamic Boarding School Kembangbelor Pacet Mojokerto. Data was obtained through interviews, observations and literature review. A significant finding from this study is the form of the santri spirituality approach which is internalized in religious, social, scientific, motivational material which is packaged in the seven keys to success and commitment of the Amanatul Ummah students. Some counclusions were made. First, the moderate religious spirituality approach which was internalized at the Boarding School went well proven by efforts to incorporate values and an implementable practice process. Second, the reason for the spirituality of the students leads to the goals and benefits of building religious-nationalist, religious-intellectual and intellectual-religious people, in accordance with Islamic ideals rooted in the Qur'an, al-Sunnah, and Islamic scholars’ convention. And finally, spirituality with optimal character through increasing faith, understanding, appreciation, and practice of Islam without forgetting to love the homeland and defend the country. Keywords: moderate spirituality of santri, amanatul ummah Islamic boarding school, religious-nationalist, religious-intellectual, intellectual-religious people